Seeing the "forest" or the "trees" of organizational justice: Effects of temporal perspective on employee concerns about unfair treatment at work - Cojuharenco, Irina (Institutional Knowledge at Singapore Management University, 2011)
What events do employees recall or anticipate when they think of past or future unfair treatment at work? We propose that an employee’s temporal perspective can change the salience of different types of injustice through its effect on cognitions about employment. Study 1 used a survey in which employee temporal focus was measured as an individual difference. Whereas greater levels of future focus related positively to concerns about distributive injustice, greater levels of present focus related positively to concerns about interactional injustice. In Study 2, an experimental design focused employee attention on timeframes that differed in temporal orientation and temporal distance. Whereas distributive injustice was more salient when future (versus past) orientation was induced, interactional injustice was more salient when past orientation was induced and at less temporal distance. Study 3 showed that the mechanism underlying the effect of employee temporal perspective is abstract versus concrete cognitions about employment.